The Intact® breast lesion excision system as a therapeutic device for selected benign breast lesions. Issue 3 (11th October 2017) - Sklair‐Levy, Miri; Rayman, Shlomi; Yosepovich, Ady; Zbar, Andrew; Goitein, David; Zippel, Douglas
Abstract: The aim of this paper is to evaluate our Unit's initial experience using the Intact breast lesion excision system as a therapeutic excision option for benign or borderline breast lesions, which otherwise would entail open operative excision. The study includes the first 111 patients who underwent therapeutic excision with the intact radiofrequency system between December 2012 and May 2016 performed at the Meirav Center for Breast Health, at the Chaim Sheba Medical Center, Ramat Gan Israel. The indications for the procedure included those patients who have benign, or atypical high risk lesions following a previous core needle biospy (CNB) who would have normally undergone conventional excision biopsy. After reviewing each case separately, we found that the use of the BLES system as a treatment device permitted the avoidance of operations that would have been otherwise indicated, in 98 cases of the total 111 in the cohort (88.3%). Thirteen cases eventually had to undergo surgical excision. In eight cases pathology was upgraded from the initial CNB to invasive or noninvasive carcinoma. Although the INTACT sysytem is most commonly used as an alternative biopsy technique for its diagnostic capabilities, this study assessed its clinical role as a definitive therapeutic excisional modality in selected cases of benign breast disease. It proved valuable in the majority of cases with avoidance of surgery where it was traditionally indicated, (98/111, 88.3%) and as definitive fibroadenoma management in a further 28 patients.